Risk Assessment of Aquifer Salinization in a Large‐Scale Coastal Irrigation Scheme, Italy. Issue 4 (18th January 2016) - Zaccaria, Daniele; Passarella, Giuseppe; D'Agostino, Daniela; Giordano, Raffaele; Solis, Samuel Sandoval
Abstract : This paper describes a study conducted on a coastal agricultural area of southern Italy to assess the impending risk of aquifer degradation related to intensive groundwater pumping by farmers. It occurs that farmers rely on groundwater pumping to offset the inadequate irrigation delivery service provided by the local water management agency. The study area is intensively farmed by small land‐holding growers with high‐value horticultural crops, whose irrigation deliveries are supplied by a gravity‐fed water distribution system operated by a local water users' organization. The soil and aquifer degradation hazards were appraised using a simplified environmental risk assessment procedure that allowed identifying the risk‐generating processes, assessing the magnitude of impacts, and estimating the overall risks significance. The investigations revealed significant aquifer salinity increase during the past years. The stakeholders' perspective on agricultural water use was collected through field interviews, and was framed using a fuzzy cognitive map, which revealed the farmers' propensity to pump groundwater rather than rely on rotational deliveries from the surface distribution system. Finally, some preliminary risk mitigation options were appraised by exploring the growers' response to possible changes of irrigation deliveries by the water users' organization. The presented study consisted of multi‐annual observations, data analysis, and modeling efforts, which jointly proved to be useful to analyze the main drivers to stakeholders' decisions and their long‐term impacts on water resources use and management. Abstract : A study is conducted on a coastal agricultural area of southern Italy to assess the risk of aquifer degradation by using field observations, information collected from farmers and irrigation system's operators, and a modeling effort. The aquifer and soil degradation in the study area are found to have high risk significance, mostly due to stakeholders' water management decisions and to farmers' propensity to rely on groundwater pumping rather than on service water. Experimental evidences suggest that mitigations of such risks could be achieved through the provision of enhanced irrigation delivery service to farmers.